Utilizing nutritional and polyphenolic compounds in underutilized plant seeds for health application - Zaini, Nur Syamimi; Karim, Roselina; Abdull Razis, Ahmad Faizal; Zawawi, Norhasnida (MDPI, 2022)
Plants represent a significant part of the human diet. Humans have utilized every part of plants for survival, and seeds are no exception. Seeds offer high protein, unsaturated fats, fibre, essential vitamins, and minerals for various food applications. They are also a promising reservoir of bioactive compounds, where various phytochemicals, such as polyphenolic compounds, capable of maintaining and improving well-being, are present in abundant quantities. Plants from Malvaceae and Cannabaceae families are known for their fibre-rich stems that benefit humankind by serving numerous purposes. For many centuries they have been exploited extensively for various commercial and industrial uses. Their seeds, which are often regarded as a by-product of fibre processing, have been scientifically discovered to have an essential role in combating hypercholesterolemia, diabetes, cancer, and oxidative stress. Maximizing the use of these agricultural wastes can be a promising approach to creating a more sustainable world, in accordance with the concept of Sustainable Development Goals (SDGs).